Legal Reformation of Tax Court in Indonesia: Reforming Legal Culture, Institutional and Legislative Aspects - Ispriyarso, Budi; Bayuseno, Athasius P.; Wahab, Harlida Abdul (International Journal of Criminology and Sociology, 2021)
This research is motivated by the many weaknesses that exist in the Ppajak court in Indonesia. Therefore, this research needs to be carried out with the aim that the tax court in the future will be better, more certain in law, and just. The problem is the reason for reforming the tax court in Indonesia and the way to reform the law on the tax court in Indonesia. The research method used is a statutory, historical, and comparative approach. The result of his research is that the tax court in Indonesia must be reformed because it contains many weaknesses. Furthermore, the findings show that tax court reform must be carried out from the aspects of legislation, institutional and legal culture. Based on the statutory aspect, synchronization of laws must be carried out. Based on the institutional aspect, institutional improvement must be carried out. Based on the aspect of legal culture, this must be done by increasing the morale of the parties. The novelty of this research is that the tax dispute settlement model is found after the tax court becomes a special court within the state administrative court. In conclusion, the tax court in Indonesia still contains many weaknesses, so it must be reformed immediately.